Endothelial dysfunction in the regulation of portal hypertension - Iwakiri, Yasuko (2011)
Portal hypertension is caused by an increased intrahepatic resistance, a major consequence of cirrhosis. Endothelial dysfunction in liver sinusoidal endothelial cells (LSECs) decreases the production of vasodilators, such as nitric oxide (NO) and favors vasoconstriction. This contributes to an increased vascular resistance in the intrahepatic/sinusoidal microcirculation. Portal hypertension, once developed, causes endothelial cell (EC) dysfunction in the extrahepatic, i.e. splanchnic and systemic, circulation. Unlike LSEC dysfunction, EC dysfunction in the splanchnic and systemic circulation overproduces vasodilator molecules, leading to arterial vasodilatation. In addition, portal hypertension leads to the formation of portosystemic collateral vessels. Both arterial vasodilatation and portosystemic collateral vessel formation exacerbate portal hypertension by increasing the blood flow through the portal vein. Pathologic consequences, such as esophageal varices and ascites, result. While the sequence of pathological vascular events in cirrhosis and portal hypertension have been elucidated, the underlying cellular and molecular mechanisms causing EC dysfunctions are not yet fully understood. This review article summarizes the current cellular and molecular studies on EC dysfunctions found during the development of cirrhosis and portal hypertension with a focus on intra- and extrahepatic circulation. The article ends by discussing future directions of study for EC dysfunctions.